Normative values for handgrip strength in Colombian children and adolescents from 6 to 17 years of age: estimation using quantile regression (2022)
Objective: The objective of this study is twofold: i) to estimate the normative values for handgrip strength and relative handgrip strength, specific to sex and age, for Colombian children and adolescents from 6 to 17 years of age using quantile regression models and ii) to compare the normative values for handgrip strength and relative handgrip strength in Colombian children and adolescents with those in children and adolescents in different countries. Method: This was a cross-sectional analysis of a sample of 2647 youngsters. Handgrip strength was evaluated with a TKK 5101 digital dynamometer (Takei Scientific Instruments Co., Ltd., Tokyo, Japan). The relative handgrip strength was estimated according to weight in kilograms. The normative values were estimated to handgrip strength and relative handgrip strength through quantile regression models for the percentiles P5, P10, P25, P50, P75, P90, and P95 developed independently for each sex. All analyses were adjusted for the expansion factor. Results: The values for handgrip strength were considerably higher in males than in females in all age ranges. Additionally, as age increased for both sexes, the values for handgrip strength increased. The percentiles by sex and age for relative handgrip strength show for males a proportional increase according to age; for females, this did not occur. Conclusions: When making comparisons with international studies, variability is observed in the methodologies used to evaluate handgrip strength and estimation methods, which could influence the discrepancies between the different reports.